Wicking behavior and dynamic elastic recovery properties of multifunction elastic warp-knitted fabrics. Issue 14 (September 2015) - Yu, Zhi-Cai; Zhang, Jian-Fei; Lou, Ching Wen; He, Hua-Ling; Chen, An-Pang; Lin, Jia-Horng
The purpose of this study was to evaluate the moisture transport and dynamic elastic recovery (DER) properties of the multifunction elastic warp-knitted fabric that may be used in electromagnetic shielding personal protective clothing (PPC) to protective wearers from electromagnetic radiation and other occupational hazards. The wicking behaviors of the produced elastic warp-knitted fabrics in terms of vertical wicking, horizontal wicking, transfer wicking, and siphon wicking abilities were discussed. The obtained results showed that increasing the amount of crisscross-section polyester yarns had a significant influence on the wicking behavior of the produced elastic warp-knitted fabrics. Moreover, the stretch and recovery properties of the produced elastic warp-knitted fabric caused by bodily movement were also assessed in terms of DER values at different extension levels of the fabric. The results indicated that increasing the extension level would affect the residual energy in the fabric and increase the stress values to the skin. These results provide a better understanding of the characteristics of these elastic knitted fabrics prior to use for tight-fit PPC.